2023
DOI: 10.3389/fimmu.2023.1088801
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping anti-NMDAR encephalitis and multiple sclerosis: A case report and literature review

Abstract: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune-mediated disease characterized by complicated neuropsychiatric symptoms and the detection of cerebrospinal fluid antibodies against the GluN1 subunit of the NMDAR. With the proposed clinical method, more anti-NMDAR encephalitis patients have been discovered since its first report. However, anti-NMDAR encephalitis overlapping with multiple sclerosis (MS) is rare. Herein we report a male patient with anti-NMDAR encephalitis who developed MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Keyword clustering mapping showed that studies in the field of anti-NMDA encephalitis were mainly centered on its definition, pathogenesis, clinical manifestations, diagnostic indicators, therapeutic modalities, and case reports, and the results confirmed that anti-NMDA encephalitis is an autoimmune-mediated disease manifesting as a complex neuropsychiatric syndrome, which results in a wide range of neurological symptoms, including psychiatric symptoms, movement disorders, memory disorders ( 14 ). And according to the clustering results, for cluster 2 we explored the specific clinical manifestations of anti-NMDA encephalitis, suggesting that patients with anti-NMDA receptor encephalitis present a characteristic stage-by-stage clinical course, and according to the course curve of classical anti-NMDAR encephalitis drawn by Kayser and Dalmau ( 32 ), we found that patients often have an antecedent infection 2 weeks before the onset of the disease, which leads to the development of certain antecedent symptoms, mainly viral cold symptoms; 1–2 weeks of progression of psychiatric symptoms, such as hallucinations, mania, delusions, anxiety, insomnia; weeks to months of neurological complications: disorders of consciousness, central hypoventilation, and even coma, often accompanied by dyskinesia and seizures; and months to years of neurological symptoms: executive functions, hypoparathyroidism and hyperventilation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Keyword clustering mapping showed that studies in the field of anti-NMDA encephalitis were mainly centered on its definition, pathogenesis, clinical manifestations, diagnostic indicators, therapeutic modalities, and case reports, and the results confirmed that anti-NMDA encephalitis is an autoimmune-mediated disease manifesting as a complex neuropsychiatric syndrome, which results in a wide range of neurological symptoms, including psychiatric symptoms, movement disorders, memory disorders ( 14 ). And according to the clustering results, for cluster 2 we explored the specific clinical manifestations of anti-NMDA encephalitis, suggesting that patients with anti-NMDA receptor encephalitis present a characteristic stage-by-stage clinical course, and according to the course curve of classical anti-NMDAR encephalitis drawn by Kayser and Dalmau ( 32 ), we found that patients often have an antecedent infection 2 weeks before the onset of the disease, which leads to the development of certain antecedent symptoms, mainly viral cold symptoms; 1–2 weeks of progression of psychiatric symptoms, such as hallucinations, mania, delusions, anxiety, insomnia; weeks to months of neurological complications: disorders of consciousness, central hypoventilation, and even coma, often accompanied by dyskinesia and seizures; and months to years of neurological symptoms: executive functions, hypoparathyroidism and hyperventilation.…”
Section: Discussionmentioning
confidence: 82%
“…Anti- N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune-mediated disease characterized by a complex neuropsychiatric syndrome, and an antibody to cerebrospinal fluid (CSF) targeting the GluN1 subunit of NMDAR exists ( 14 , 15 ), a brain parenchymal inflammation associated with autoimmune-related neurologic dysfunction ( 16 ). Anti-NMDA receptor encephalitis was first reported in 2005, when symptoms of psychotic features, memory loss, and altered consciousness were found in four young women with ovarian teratomas ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focal abnormalities were found in three patients while extreme delta brush was only observed in one patient. [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with overlapping MS, the average age of onset is slightly higher (31) and our patient’s age deviates even more significantly from the typically younger patient population. [6] , [25] , [26] In some cases, anti-NMDAR encephalitis occurs before MS, while in the majority of cases, the encephalitis occurs during the course or even a relapse of MS, suggesting a potential triggering effect of MS on anti-NMDAR encephalitis. [22] This might be due to demyelination exposing neuronal antigens, which in turn trigger an intrathecal immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation